Clinical impact of beta-blockers at discharge on long-term clinical outcomes in patients with non-reduced ejection fraction after acute myocardial infarction. Issue 1 (January 2023) - Sakagami, Azusa; Soeda, Tsunenari; Saito, Yoshihiko; Nakao, Koichi; Ozaki, Yukio; Kimura, Kazuo; Ako, Junya; Noguchi, Teruo; Suwa, Satoru; Fujimoto, Kazuteru; Dai, Kazuoki; Morita, Takashi; et al.
Abstract: Background: Beta-blockers are associated with several clinical benefits in patients with reduced left ventricular ejection fraction (REF) after acute myocardial infarction (AMI), such as lower rates of mortality, recurrence of myocardial infarction, and heart failure. However, the long-term prognosis of beta-blockers has rarely been investigated in patients with non-REF after AMI. This study aimed to investigate the clinical benefits of beta-blockers in these patients. Methods: A total of 3281 consecutive patients who were hospitalized within 48 h after AMI were registered in the J-MINUET study. Patients who underwent primary percutaneous coronary intervention (PCI) and had a left ventricular ejection fraction ≥40 % were enrolled, and patients who died during admission were excluded. Included patients were divided into two groups according to the prescription of beta-blockers at discharge. Their characteristics and clinical outcomes were compared. Results: The number of AMI patients treated with beta-blockers was 1353 (70.4 %). Patients who received beta-blockers were younger and had a higher incidence of hypertension, dyslipidemia, and ST-segment elevation myocardial infarction than those who did not receive beta-blockers. The peak creatine kinase level after primary PCI was significantly higher in patients who received beta-blockers. These patients also had a lower incidence of a composite of all-cause death, myocardial infarction, and stroke compared to those that did not receive beta-blockers (7.3 % vs. 11.9 %, p = 0.001). Multivariate analysis showed that beta-blocker use was an independent factor for better clinical outcomes. Conclusions: The J-MINUET study revealed the clinical benefit of beta-blockers in AMI patients with non-REF after primary PCI. Graphical abstract: Unlabelled Image Highlights: The J-MINUET trial is a prognostic study of patients diagnosed with acute myocardial infarction (AMI) based on the new definition. Beta-blockers improved the composite endpoint in AMI patients without reduced left ventricular (LV) dysfunction. Beta-blockers did not affect the incidence of heart failure in patients without LV dysfunction.